High Performance Controller for 100HP Grade Agricultural Vehicles - Suh, Ki-Bum; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this paper, the high performance controller design which can handle all the electric components in agricultural vehicle is proposed and implemented.Methods/Statistical analysis: To test the controller, we made the environment for testing the developed controller and monitored the responses using CAN Bus.Findings: By introducing RTOS, simultaneous response of all 12 inputs is possible. By introducing the power management module, standby current is maintained in the unit of uA.Improvements/Applications: It can be used for agricultural tractor for any vendor.Â